A systematic review of the use of computers in the management of hypertension. Issue 8 (August 1998) - Montgomery, A A; Fahey, T
Abstract : STUDY OBJECTIVE: To assess the effect of computers and computer-based clinical decision support systems on the management of hypertension. DESIGN: Systematic review of randomised controlled trials. SETTING: Ambulatory hypertension clinics, community-based health centres, and general practices. PARTICIPANTS: 11, 962 patients enrolled in seven trials retrieved from a systematic search (electronic databases, contact with authors, reference lists; no restriction on language). MAIN RESULTS: Individual trials report on a diverse population of patients (newly diagnosed or established hypertensive patients), interventions (computers used for case finding, recall and registration, feedback on quality of blood pressure control and prescribing information), and outcomes (administration, physician performance and blood pressure control). Four of five trials reported an improvement in patient administration using a computer. Two of three trials reported an improvement in physician performance using a computer. Two of six trials. reported an improvement in blood pressure control in patients using a computer. However, positive findings in two trials should be regarded cautiously because of the potential effects of cluster randomisation. CONCLUSIONS: It seems that computers have a favourable effect on the uptake and follow up of patients in hypertension management. The effect of computers on physician knowledge, recording of information, and blood pressure control in patients is less conclusive and further studies are required.